Apprentice poaching in regional labor markets - Bastian Stockinger; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
A number of studies have found that firms provide less training if they are located in regions with strong labor market competition. This finding is usually interpreted as evidence of a higher risk of poaching in these regions. Yet, there is no direct evidence that regional competition is positively correlated with poaching. Building on a recently established approach to ex-post identify poaching of apprenticeship completers, our paper is the first to directly investigate the correlation between regional labor market competition and poaching. Using German adminis-trative data, we find that competition indeed increases training establishments' probability of becoming poaching victims. However, poaching victims do not change their apprenticeship training activity in reaction to past poaching. Instead, our findings indicate that the lower training activity in competitive regions can be attributed to lower retention rates, a less adverse selection, and lower labor and hiring costs of apprenticeship completers hired from rivals.
Keywords: J24; M51; M53; R23; 330; poaching; firm-sponsored training; apprenticeship; regional labor markets; labor market competition